PREVALENCE OF SMOKING IN ADULT POPULATION OF IRKUTSK - E. B. Babanskaya (Scientific Сentre for Family Health and Human Reproduction Problems, 2016)
Smoking is a significant risk factor of chronic noncommunicable diseases. Smoking prevalence is variable in different populations. A study of the prevalence of this risk factor allows to estimate its contribution to the development of cardiovascular pathology, to plan the necessary amount of medical care for people using tobacco, and to determine the effectiveness of prevention activities in the region. As a result of the study, smoking frequency in population of the Irkutsk region older 18 years of age or over was established as 29.5 %. The number of smokers increased with age, reaching maximum value of 38.6 % in the group 30-39 years. Male smokers made maximum in the age group 30-39 years, women - in the age group of 18-19 years. The average age of smokers was 34 years, the one of nonsmokers - 43 years. The age difference was 9 years, and it was lower in the group of men than in the group of women (5 and 11 years, respectively). The number of the smoking men were 3 times larger, than women: 50.2 % and 13.5 %, respectively. Among persons with arterial hypertension, 22.1 % were smoking with the maximum frequency of smoking in age groups from 20 to 49 years. These figures point to a considerable problem of smoking in the region.